Analyzing Functionalities for Online Questionnaire System (OQS) - Atown, Hyder Yahya (2012)
In these days, and after the rapid development of information systems make the researchers are looking an easy and automate way to analysis a data collection in a questionnaire that enables researchers to obtain the results quickly instead of using manual way. Questionnaires are used in a wide range of settings to gather information about the views and behavior of individuals to inform people about the specific issues. Feedbacks of the questionnaires are used by the researcher to find an accurate result with supporting of statistical analysis functionalities. In addition, there is a strong relationship between questionnaire and research, which is questionnaire the most important phase in research activities. Consequently, this project focuses on the development of the questionnaire system by focusing on the 'built-in' statistical analysis functionalities to facilitate and support the researcher’s tasks. The Online Questionnaire System is developed in order to reduce loss of papers, time and effort. The general design methodology is represented by using Unify model language (UML). Moreover, the system has been tested based on usability and flexibility and evaluated by using questionnaires that answered by the students. A percentage of 55.2% percent and 44.8% percent answered useful and very useful respectively of the proposed model. As a conclusion it is found the respondents agree with use statistical analysis functions in Online Questionnaire website.